2021
DOI: 10.1371/journal.pone.0250738
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin-mineral supplements do not guarantee the minimum recommendations and may imply risks of mercury poisoning in dogs and cats

Abstract: Given the importance of using the vitamin-mineral supplements to guarantee the minimum nutritional recommendations for pets in homemade foods, and hypothesizing that these products may contribute to toxic metals contamination, the present study aimed to determine the concentrations of essential minerals and toxic metals in vitamin-mineral supplements available in the Brazilian market and calculate if the amount recommended by the manufacturer guarantees the minimum recommendations of NRC (2006) and FEDIAF (202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Most vitamin and mineral supplements, in the amounts recommended by manufacturers, do not guarantee the minimum nutritional recommendations for the following elements: calcium, potassium, magnesium, sodium, phosphorus, selenium and zinc. In study by Zafalon et al 38 most vitamin and mineral supplements have been found to fall short of minimum recommendations for the most important minerals, and when formulated by untrained professionals, even with supplementation, homemade food may still be deficient in nutrients. Moreover, some analyzed vitamin and mineral supplements may suggest a risk of mercury poisoning in domestic animals 38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most vitamin and mineral supplements, in the amounts recommended by manufacturers, do not guarantee the minimum nutritional recommendations for the following elements: calcium, potassium, magnesium, sodium, phosphorus, selenium and zinc. In study by Zafalon et al 38 most vitamin and mineral supplements have been found to fall short of minimum recommendations for the most important minerals, and when formulated by untrained professionals, even with supplementation, homemade food may still be deficient in nutrients. Moreover, some analyzed vitamin and mineral supplements may suggest a risk of mercury poisoning in domestic animals 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In study by Zafalon et al 38 most vitamin and mineral supplements have been found to fall short of minimum recommendations for the most important minerals, and when formulated by untrained professionals, even with supplementation, homemade food may still be deficient in nutrients. Moreover, some analyzed vitamin and mineral supplements may suggest a risk of mercury poisoning in domestic animals 38 . Our research did not detect the presence of Co, Cr, Ni.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation